Review of under-voltage load shedding schemes in power system operation [Metody UVLS w zastosowaniu do monitorowania stabilno?ci systemu energetycznego I zapobiegania jego zapa?ciom] - Verayiah R.; Mohamed A.; Shareef H.; Zainal Abidin I. (Wydawnictwo SIGMA - N O T Sp. z o.o., 2023)
A voltage collapse event is complex and localized in nature, but its effect is extensive. A vital effect of voltage collapse is total system collapse or blackouts, which will result in a significant loss to utility companies. Online monitoring of power system stability has thus become an important factor for electric power utilities. The final resort prevent the occurrence of a voltage collapse incident is the implementation of an undervoltage load shedding (UVLS) scheme. This paper focuses on the introduction of the UVLS scheme and presents an overview of the principles of the UVLS that are crucial to the design of such a protection scheme. This paper also presents the existing industrial practices and other research methods available to date.